(3QSGdI aj JMbjb GdCeQ GdeGVj GdKdGKj GdeYJd GddGe hGdaGA hGh Ch GdYjf geRIs ((3eMeO Hf GdMSf GdHfGfj s)
(3ChdgG (B:s
(3gPg GdCHjGJ JTJed Ydi JMbjb GdCeQ GdeGVj, GdKdGKj GdeYJd GddGe hGdaGA hGh, Ch GdYjf geRI s
(3BNQgG (B:s
(3hEfeG JQcJ GdJeKjd HGdUjZ eDcOI hZjQ eDcOI gPG BNQ eG bUOfGg hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B85 - (3U(B90s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B134 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(1032 (3O(B) s
Keywords: (3GdfMhs